Pengaruh The Flower Of Service dan Physical Evidence terhadap Loyalitas Konsumen pada Starbucks Coffe - ., Carissa; ., Sulistiono (Jurnal Ilmiah Manajemen Kesatuan, 2017)
The concept of Flower of Service was first introduced by Christopher Lovelock, a British service marketing expert. According to this concept, value is constructed by core products and supplementary services. There are two identified supplementary service, first is a supplementary service that acts as deliverer of service or aid in the usage of core products. And second is a supplementary service that strengthens and adds value to the customers. Mean while, physical evidence is recognized as one of the many factors that influence the customers to buy or use the offered services, and customers’ loyalty is a chance for the buyers to become a loyal customers and /or clients. This research is aimed to (1) find out about the influence of flower of service on customers’ loyalty, (2) to examine the influence of physical evidence on customer loyalty, and (3) to find out the influence of flower of service and physical evidence on customer loyalty. The research show that the multiple linear regression equation Y=3,786+0,482 X1+0,348 X2 which means that if flower of service is represented with 1 then the level of customers’ loyalty will increase for an amount of 0,482 and if physical evidence is 1 then the level of customers’ loyalty will increase for an amount of 0,348. The result of coefficient correlation analysis show that r = 0,642 which means that there is a significant relationships between flower of service and physical evidence on customers’ loyalty. The analysis for the coefficient determination proves that flower of service contributes 41,2% in creating customers’ loyalty and the rest of 58,8% was determined by other factors.